Efeito do inibidor da fosfodiesterase tipo 4 na recuperação da função erétil e regeneração nervosa após lesão do nervo cavernoso em ratos - Linhares, Bruno Lima (2023)
There is no consensus on the best treatment regimen for recovery of erectile function (EF) after radical prostatectomy (RP). Although many pharmacological interventions can improve EF in rats, there is still a lack of studies evaluating strategies that promote nerve regeneration of the cavernous nerve (CN). Phosphodiesterase type 4 inhibitors(IPDE4), such as rolipram, have shown a neuroprotective effect after spinal cord injury in mice, facilitating functional recovery. It has also been suggested that the neuroprotective property of sildenafil is probably attributed to its effect on phosphodiesterase type 4. Our aim was to evaluate the role of IPDE4 in EF recovery and nerve regeneration after bilateral CN crush injury in rats (BCNI). Thirty male Wistar rats were randomly divided into four groups: (i) sham (no CN lesion); (ii) control (no treatment after BCNI); (iii) BCNI + tadalafil; (iv) BCNI + rolipram and (v) BCNI + tadalafil + rolipram. The initial laparotomy was performed and the CN were crushed with a hemostatic clamp. The animals in groups (iii) and (iv) received tadalafil (5mg/kg/d) or rolipram (1mg/kg/d) orally for 14 days, respectively. The animals in group (v) received tadalafil + rolipram at the same doses. Then, the animals were submitted to CN stimulation at frequencies 4, 8 and 16 Hz, with recording of mean arterial pressure (MAP) and intracavernosal pressure (ICP). EF was represented by the measurement of maximum ICP normalized to MAP (ICP/MAP ratio) and total normalized area under the curve (AUC) of ICP. The penis and CN of the animals were sent for structural evaluation with the immunohistochemical markers S100 and Ki-67. In the functional analysis, BCNI resulted in worse EF when compared to sham. No significant differences were found in the ICP/MAP ratio when comparing groups (iii), (iv) or (v) with the control group. When considering AUC of ICP (AUCICP), the rats treated with tadalafil showed a significant improvement in the EF. The animals that received rolipram showed a trend towards an improvement in the AUCICP/MAP ratio compared to the control group, but the difference did not reach statistical significance. The tadalafil group had a higher expression of S100 in the dorsal penile nerve compared to the control group (p<0.05). The rolipram group had a lower expression of Ki-67 in the CN compared to the control group (p<0.05). In the experimental model, rolipram did not improve erectile response after CN injury in rats. Additional studies are needed to evaluate the role of IPDE4 in nerve regeneration after CN injury and their therapeutic potential in post-RP erectile dysfunction.